The effect of damping and force application point on the non-linear dynamic behavior of a cracked beam at sub- and super-resonance vibrations - Bovsunovskii, A.P.; Surace, P.; Bovsunovskii, O.A. (Проблемы прочности, 2006)
The finite element model of an elastic body with a closing crack is presented. Using this model, we show that the non-linear distortions of vibrations at superharmonic and subharmonic resonances are the high sensitive indicators of crack presence. The intensity of these indicators manifestation substantially depends on the level of damping in the system and on the load application point. Представлено скінченноелементну модель пружного тіла з тріщиною, що закривається. Показано, що нелінійні спотворення коливань при супер- і субгармонічному резонансах е високочутливим проявом наявності тріщини. Інтенсивність цього прояву суттєво залежить від рівня демпфування в системі та від місця прикладення вимушеної сили. Представлена конечноэлементная модель упругого тела с закрывающейся трещиной. Показано, что нелинейные искажения колебаний при супер- и субгармоническом резонансах являются высокочувствительным проявлением наличия трещин. Интенсивность этого проявления существенно зависит от уровня демпфирования в системе и места приложения вынуждающей силы.